Sustainable contribution of “oregano” to the well-being of poultry producers (GnosisWisdom, 2025)
The use of oregano (Origanum vulgare) in chicken health has established itself as a natural alternative to growth-promoting antibiotics, whose indiscriminate use has raised concerns about the antimicrobial resistance they represent. This literature review analyzes the latest scientific evidence on the functional properties of oregano and its impact on avian health. Positive effects of oregano essential oil were identified in the control of enteric pathogens such as Salmonella spp. and Clostridium perfringens, attributable to bioactive compounds such as carvacrol and thymol. In addition, its antioxidant and anti-inflammatory action contributes to improved intestinal integrity, reduced oxidative stress, and reduced inflammatory processes. At the immunological level, oregano stimulates the production of immunoglobulins and strengthens the immune response to common infections in poultry farming. Zootechnical improvements have also been observed, such as increased body weight, better feed conversion, and higher egg quality; however, challenges remain related to dose standardization, chemical variability, and evaluation of long-term effects. Overall, the findings support the use of oregano as an effective and sustainable tool for promoting poultry health and productivity without the adverse effects of conventional antibiotics.
Keywords: Origanum vulgare; avian health; phytobiotic; alternative antibiotics